Insights into the cellular pharmacokinetics and pharmacodynamics of thiopurine antimetabolites in a model of human intestinal cells. (25th September 2021) - Genova, Elena; Lucafò, Marianna; Pelin, Marco; Di Paolo, Veronica; Quintieri, Luigi; Decorti, Giuliana; Stocco, Gabriele
Abstract: Thiopurines, immunomodulating drugs used in the management of different chronic autoimmune conditions and as anti-leukemic agents, may exert in some cases gastrointestinal toxicity. Moreover, since these agents are administered orally, they are absorbed across the gastrointestinal tract epithelium. On these premises, cellular and molecular events occurring in intestinal cells may be important to understand thiopurine effects. However, quantitative information on the biotransformation of thiopurines in intestinal tissues is still limited. To shed light on biotransformation processes specific of the intestinal tissue, in this study thiopurine metabolites concentrations were analyzed by an in vitro model of human healthy colon, the HCEC cell line, upon exposure to cytotoxic concentrations of azathioprine or mercaptopurine; the investigation was carried out using an innovative mass spectrometry method, that allowed the simultaneous quantification of 11 mono-, di-, and triphosphate thionucleotides. Among the 11 metabolites evaluated, TIMP, TGMP, TGDP, TGTP, MeTIMP, MeTIDP and MeTITP were detectable in HCEC cells treated with azathioprine or mercaptopurine, considering two different incubation times before the addition of the drugs (4 and 48 h). Different associations between metabolites concentrations and cytotoxicity were detected. In particular, the cytotoxicity was dependent on the TGMP, TGDP, TGTP and MeTITP concentrations after the 4 h incubation before the addition of thiopurines. This may be an indication that, to study the association between thiopurine metabolite concentrations and the cytotoxicity activity in vitro, short growth times before treatment should be used. Moreover, for the first time our findings highlight the strong correlation between cytotoxicity and thiopurine pharmacokinetics in HCEC intestinal cells in vitro suggesting that these cells could be a suitable in vitro model for studying thiopurine intestinal cytotoxicity. Highlights: Quantification of 11 phosphorylated thionucleotides in intestinal cells by LC-MS/MS. Cytotoxicity dependent on metabolite levels only after the 4 h pre-incubation. Thiopurine cytotoxicity and metabolites levels, a strong correlation detected. HCEC line as a suitable in vitro model for thiopurine intestinal cytotoxicity.